Does civil servant teachers’ job satisfaction influence their absenteeism? - Purwani Puji Utami; Alexius Dwi Widiatna; Herlyna Herlyna; Alpha Ariani; Faridah Karyati; Ardya Setya Nurvrita (International Journal of Evaluation and Research in Education (IJERE), 2021)
The present research aimed at investigating the direct effect of civil servant teacher job satisfaction on their absenteeism. Quantitative approach with survey method was employed. The sample involved was 198 civil servant teachers from public senior high schools in Bekasi, West Java, Indonesia. The result signified that tcount < ttable (-2.84<-1.97) leading to the acceptance of H0 and the rejection of H1. This explicitly stated that civil servant job satisfaction has a negative direct effect on their absenteeism. For job satisfaction predictors, positive attitude places the highest position followed by comfort in work and certainty in work. While the highest predictors of absenteeism from the highest to the lowest are: punctual task completion failure, absenteeism style, and no explanation absence. The study is predicted to provide recommendation for schools to promote teacher job satisfaction and suppress their absenteeism rate. Providing comfort and creating positive working atmosphere for teachers either has significant consequence to endeavor job satisfaction promotion and absenteeism rate decrease. Besides, leaders and school management board assertiveness in the mechanism of decreasing absenteeism is unarguably decisive to create fairness in policy and procedure obedience.